Customer relationship management dan Customer trust dalam Membangun Loyalitas Pelanggan Melalui Kepuasan Pengguna GoPay - Andreas Kristian Bayu Dwi Chayono; Ana Kadarningsih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study investigates the influence of Customer Relationship Management (CRM) and Customer Trust (CT) on Customer Satisfaction and Customer Loyalty among GoPay users in Indonesia. Employing a quantitative approach with Structural Equation Modeling (SEM) using Smart PLS, data were collected from 160 respondents selected through purposive sampling. The findings reveal that CRM significantly affects Customer Satisfaction (β = 0.492; p < 0.001) and Customer Loyalty (β = 0.476; p < 0.001), while CT has a significant impact on Customer Satisfaction (β = 0.408; p < 0.001) but not on Customer Loyalty (β = 0.095; p = 0.333). Additionally, Customer Satisfaction significantly mediates the relationship between CRM and Customer Loyalty (β = 0.196; p = 0.008), and between CT and Customer Loyalty (β = 0.163; p = 0.008). These results underscore the vital role of CRM and trust in enhancing customer satisfaction, which in turn fosters loyalty. The study offers theoretical insights by confirming the mediating role of satisfaction and provides practical recommendations for digital wallet providers to improve customer retention through trust-building and personalized relationship strategies.